Sex differences in ventricular remodeling and long-term heart failure outcomes following acute coronary syndrome. (25th November 2020) - Adamson, P; Verryt, T; Frampton, C.M; Troughton, R; Doughty, R.N; Richards, A.M
Abstract: Background: Compared with men, women are at increased risk of heart failure hospitalization following acute coronary syndrome (ACS). Purpose: We sought to determine whether this increased hazard was associated with differing patterns in left ventricular (LV) remodeling over the first 12 months after ACS. Methods: In a prospective multi-centre observational cohort study, 2, 140 patients with ACS underwent echocardiography at 1, 4, and 12 months following the index event. Heart failure hospitalisation events were captured over a median 4.8 (IQR 3.4–6.5) years and relative risk compared between women and men using a multivariable Cox model adjusted for baseline demographics (age and systolic blood pressure) and echocardiographic variables (LV end diastolic and end systolic volumes, LV ejection fraction, interventricular septal wall thickness, and E/e') captured at baseline and 12 months. Results: The 609 (28.5%) women were older (mean [SD] age 70 [12] versus 65 [12] years), had higher systolic blood pressure, demonstrated smaller increases in peak myocardial biomarkers, and were less likely to undergo coronary revascularization during the index admission (41.9% versus 62.0%; p<0.001 for all). After indexing for body surface area, women had smaller LV end diastolic and end systolic volumes, greater LV ejection fractions, and greater septal wall thickness and diastolic filling pressure estimates (E/e' 14 versus 11; p<0.001 for all). Diastolic volumes further diverged at 12 months (p=0.05) and septal wall thickness increased compared with men (p=0.016). In unadjusted and adjusted analyses women were at increased risk of future heart failure hospitalization (unadjusted HR 1.5, 95% CI 1.2–1.9, adjusted HR 1.6, 95% CI 1.1–2.4). Conclusions: Women experience a more concentric remodeling pattern over the 12 months following ACS. Women remain at increased risk of long-term heart failure hospitalization after accounting for clinical and echocardiographic characteristics. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): National Heart Foundation of New Zealand, New Zealand Health Research Council